Green Area Requirement in Zoned Areas: The Case of Niğde City - Gülden Sandal Erzurumlu; Burak Şen (Turkish Journal of Agriculture: Food Science and Technology, 2019)
Currently half the world population lives in cities, and this proportion is expected to increase rapidly to 70% over the next years. Multi-storey buildings and small green areas are being created with the effect of increasing population for years. In urban areas, where there are fewer green areas compared to rural areas, human diseases are increasing. Increased health problems affect people negatively and the need for green spaces increases. According to the regulation published in 1999, the amount of green area per person is determined as 10 m2. For this reason, the green areas designed in the sites where high-rise buildings have increased in the areas opened for reconstruction in Niğde will be evaluated. Accordingly, we will be determined adequacy of the green area. This study was conducted to determine the importance of green spaces for health and to provide suggestions for further research.